The diffusion of the sandbox approach to disruptive innovation and its limitations - TSAI, Chang-Hsien (Institutional Knowledge at Singapore Management University, 2021)
Faced with the challenges posed by disruptive technologies and innovations, many countries have adopted different regulatory approaches, institutional structures, and norms to maximize benefits and mitigate risks. Among such regulatory endeavors, the regulatory sandbox, first adopted by the United Kingdom in its financial sector, stands out as a prominent mechanism to strike a balance between promoting technological innovations and ensuring market order. Given the promises of the regulatory sandbox, there has been a gradual embrace of this approach by governments across continents, arguably indicating a global norm diffusion. There is also a trans-governmental endeavor to facilitate cooperation among regulators and regulatory convergence through bilateral arrangements and the multilateral “global sandbox” club. Beyond the financial sector, due to the cross-border nature and implications of many disruptive technologies and innovations, some countries have applied similar approaches to nonfinancial areas. This Article discusses examples of different approaches in Canada, Japan, Singapore, and Taiwan in areas such as energy, the environment, health care, and transportation. These developments evidence the rise of the sandbox approach to regulate disruptive technologies and innovations in different sectors at the national, trans-governmental, and global levels, which has crucial theoretical and practical implications.